2020
DOI: 10.13189/ujer.2020.081050
|View full text |Cite
|
Sign up to set email alerts
|

Teacher's Innovative Behavior in Indonesian School: The Role of Knowledge Management, Creativity and OCB

Abstract: Innovation, especially innovative behavior, has become a vital interest among teachers in Indonesia, as it argues to play a prominent role in increasing work quality and effectiveness, particularly, tasks of teaching. However, empirical evidence assessing innovative behavior is still relatively limited, so it explores the effect of knowledge management (KM) and creativity on innovative behavior mediating by organizational citizenship behavior (OCB). A questionnaire collected the research data through a survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…This surprising result was inconsistent with previous research, which revealed a positive relationship between teaching resources and teacher innovation in schools in both traditional and online teaching environments (Eteokleous, 2008;Thurlings et al, 2015). As innovation is a complex multiple-stage process that involves idea exploration, idea generation, championing, and implementation and requires greater creative support (Kleysen and Street, 2001;Widodo and Gustari, 2020), it is challenging to stimulate teachers' willingness to teach innovatively in higher education (Cao et al, 2020). This is especially the case for university EFL teachers, most of whom do not have online teaching experience (83.5% in our study); thus, they may feel exhausted, less innovative, and overloaded when required to deliver online courses with very little time to prepare and to select suitable teaching platforms and teaching methods from an overwhelming supply of available teaching resources.…”
Section: The Relationships Between Teaching Support Teacher Innovation and Teaching Satisfactionmentioning
confidence: 57%
“…This surprising result was inconsistent with previous research, which revealed a positive relationship between teaching resources and teacher innovation in schools in both traditional and online teaching environments (Eteokleous, 2008;Thurlings et al, 2015). As innovation is a complex multiple-stage process that involves idea exploration, idea generation, championing, and implementation and requires greater creative support (Kleysen and Street, 2001;Widodo and Gustari, 2020), it is challenging to stimulate teachers' willingness to teach innovatively in higher education (Cao et al, 2020). This is especially the case for university EFL teachers, most of whom do not have online teaching experience (83.5% in our study); thus, they may feel exhausted, less innovative, and overloaded when required to deliver online courses with very little time to prepare and to select suitable teaching platforms and teaching methods from an overwhelming supply of available teaching resources.…”
Section: The Relationships Between Teaching Support Teacher Innovation and Teaching Satisfactionmentioning
confidence: 57%
“…They could develop and change themselves to organize effective learning management which responded to different educational contexts. As reported by Dyer [15], creating the efficient idea network helped innovators create processes, products, and services which were advantages: similarly, the study of Widodo and Gustari [16] reported that Knowledge Management, creativity, and Organizational Citizenship Behavior were essential antecedents for innovative behavior.…”
Section: Networkingmentioning
confidence: 74%
“…For example, teachers who have a strong affective commitment will tend to easily actualize their potential This empirical fact indicates that improving AQ, interpersonal communication, and organizational commitment will encourage an increase teachers' OCB so that primary school principals have an interest in making breakthrough efforts and strategic policies to improve teachers' AQ, interpersonal communication and organizational commitment. This is very important because, according to various studies that OCB has been proving to improve innovative behavior, productivity, performance, and organizational effectiveness [1]- [4].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies recently indicated that OCB affects employees' productivity [1] and performance [2], then implicate to organizational performance [3]. In an educational context, OCB also influences teachers' innovative behavior [4]. It means OCB is essential for teachers, so it needs and urgent to investigates, primarily considering that teachers in Indonesia have not shown extra behavior that can encourage the achievement of optimal quality education.…”
Section: Introductionmentioning
confidence: 99%